2018
DOI: 10.15244/pjoes/75160
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Fire Hazards Due to Landfill Gas Generation and Emission

Abstract: The last and the only national-level data on waste composition and amount in Serbia dates back to 2010, when the Serbian Government adopted a waste management strategy from 2010 to 2019. With representative samples from 160 municipalities, it was estimated that 0.87 kg/ capita/day of waste was generated in Serbia, which amounted to 318 t/day [1]. By comparison, waste generation in Turkey (Kocaeli) is 0.92 kg/capita/day, in Austria (Vienna) 1.50 kg/capita/day, and in the USA (New York) it is 2.58 kg/capita/day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Just like in other studies [32][33][34]15], the perceived health risks reported by the respondents in this study included; smoke emanating from burning waste, odour from rotting organic waste, providing an habitat for breeding mosquitoes, and harboring other disease vectors (Fig. 3).…”
Section: Perceived Health Risks Associated With Waste Dumping At Kalu...mentioning
confidence: 93%
“…Just like in other studies [32][33][34]15], the perceived health risks reported by the respondents in this study included; smoke emanating from burning waste, odour from rotting organic waste, providing an habitat for breeding mosquitoes, and harboring other disease vectors (Fig. 3).…”
Section: Perceived Health Risks Associated With Waste Dumping At Kalu...mentioning
confidence: 93%
“…To summarize Figure 4, when the gas conditions are unsafe, the temperature should be higher. Milosevic et al [56] observed O 2 concentrations of 15 to 21.2% v/v (more than double the reference O 2 volume of 5%) in gas-wells, whereas the gas-well temperature ranged from 24.9 to 48.9 • C and the fire probability ratio decreased by 0.836 with an increase in the CH 4 -to-CO 2 ratio concentrations. Another study [16] also found similarly high O 2 levels (15-21.2% v/v) corresponding with gas-wells in both cool temperature and SET areas.…”
Section: Testing the Effect Of Each Variable On Temperaturementioning
confidence: 96%
“…Among the four parameters, the CH 4 -to-CO 2 ratio is the covariate showing the strongest association with the temperature ranges with a significance level less than 0.001. Using a univariate logistical regression to study the synergistic effect of fire indicators, Milosevic et al [56] found the CH 4 -to-CO 2 ratio concentration to be a statistically significant fire indicator. The first tree branch starting with a ratio of <1, shows a strong association with O 2 (significance level, p < 0.001), whereas CH 4 was strongly associated (significance level, p < 0.001) with the branch of a ratio of >1.…”
Section: Decision Tree Analysismentioning
confidence: 99%
“…The thermal radiation from a fire in a landfill site can be intense and make it very difficult for firefighters to approach its source to apply extinguishing media. Owing to these reasons their characteristics and mitigation measures have been receiving attention from the recent research fraternity (Chavan et al, 2019;Manjunatha et al, 2020;Mikalsen et al, 2021;Milosevic et al, 2018;Mazzucco et al, 2020;Morales S et al, 2018).…”
Section: Introductionmentioning
confidence: 99%